Perubahan Interaksi Masyarakat Desa (Studi Kasus Pasar Papringan Dusun Ngadiprono, Ngadimulyo, Kedu, Kabupaten Temanggung): Changes in Rural Community Interaction (Case Study Papringan Market in Ngadiprono, Ngadimulyo, Kedu, Temanggung) - Al Ghozali, Randy Ardana; Murdiyanto, Eko (Journal of Agricultural Social and Business, 2025)
This study aims to Examine the changes in rural community interactions in the precense of Papringan Market Ngadiprono, Ngadimulyo, Kedu, Temanggung. This study uses a qualitative approach with a case study type of research. The informant determination technique was carried out by purposive sampling. Sources of data used are primary data and secondary data. Data collection techniques using observation, interviews, and documentation. Testing the validity of the data using source triangulation. The data analysis technique used is data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that The interactions among the people of Ngadiprono, the market visitors, and the people of Ngadidono led to adjustments within the Ngadiprono community, resulting in changes in social contact and communication. Direct interactions continued, but there was also an addition of indirect interactions using media such as WhatsApp. In the process, there were conflicts, interventions, and competition both within the village and with people from outside the village. However, despite these challenges, the people of Ngadiprono were ultimately able to establish good cooperation, even with the people of Ngadidono. Thanks to the Papringan Market, the community now has alternative livelihoods, is more accustomed to using modern tools, and has become more skilled in both crafts and language.